New Quantum Burst-Error Correcting Codes from Interleaving Technique - Trinca, Cibele Cristina; De Albuquerque, Clarice Dias; Junior, Reginaldo Palazzo; Interlando, J. Carmelo; De Andrade, Antonio Aparecido [UNESP]; Watanabe, Ricardo Augusto (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Quantum memory is essential for the development of many devices in quantum information processing, including a synchronization tool that can match the various processes in a quantum computer, a quantum gate that maintains the identity of any state, and a mechanism for converting predetermined photons into on-demand photons. Quantum memory can be used in many aspects, such as quantum computing and quantum communication. Continuous research and experiments have enabled quantum memory to realize the storage of qubits. On the other hand, interleaving techniques are used to deal with burst of errors. Many works from literature provide effective interleaving techniques for combating burst of errors by using classical error-correcting codes. However, to the best of our knowledge, little is known regarding interleaving techniques for combating cluster of errors in topological quantum error-correcting codes. Thenceforward, it is proposed in this work a new interleaving technique by using good toric quantum codes, namely Bombin and Martin-Delgado toric codes and another class of toric codes from literature which is described in this work. As a consequence, by applying this new interleaving method to such toric quantum codes, new quantum burst-error correcting codes are obtained which improve the coding gain. In addition to the proposed quantum interleaving technique improves such parameter, it can be used for burst-error correction in errors which are located, quantum data stored and quantum channels with memory.
Keywords: polyomino; quantum burst-error cor-rection; quantum interleaving; square lattice; toric quantum codes